Influence of choline chloride-based NADES on the composition of Myristica fragrans Houtt. essential oil. Issue 5 (May 2022) - Lanari, Daniela; Zadra, Claudia; Negro, Francesca; Njem, Rima; Marcotullio, Maria Carla
Abstract: Natural deep eutectic solvents (NADES) have emerged as green extracting solvents in recent years. In this study, a variety of choline chloride (ChCl)-based natural deep eutectic solvents (NADES) were used as co-solvents for the hydrodistillation of nutmeg with the aim to obtain M. fragrans essential oil (EO) in higher yield and with a lower content of toxic phenylpropenoids (e.g. myristicin and safrole). The influence of ChCl-based NADES as additives in the hydrodistillation process was studied. The results showed that NADES additives improved the yield of the extracted essential oil and influenced its composition leading to a decrease in toxic phenylpropenoids. Best results were achieved by using ChCl-CA NADES ultrasound-assisted pretreatment coupled with traditional 2 ​h Clevenger hydrodistillation that increased the yield of the EO from 0.98% (traditional) to 1.41% and a decrease of the phenylpropenoids amount in the essential oil. Graphical abstract: Image 1 Abstract : Myristica fragrans ; Nutmeg; Essential oil; NADES; Choline chloride, Ultrasound pretreatment.